Experimental and Numerical Study on Cold-formed Steel Built-up Box Beams - Bunya Chea; Taweep Chaisomphob; Wasan Patwichaichote; Eiki Yamaguchi (Institut Teknologi Sepuluh Nopember, 2017)
In this paper, a study of flexural behavior of cold-formed steel built-up box beam which is commonly used in low rise and residential building is presented. Experimental investigation is conducted to understand about the failure mode and the load capacity of the beam in this study. Numerical analysis by using ABAQUS program was performed in order to verify with experimental result. In addition, influence of thickness, connection spacing, and web height and flange width to thickness ratio, affecting load capacity and buckling behavior of the beam, were discussed. The result shows that the finite element analysis can well predict the flexural strength of the beam and the thickness and connection spacing are the key factors to improve load capacity of the beam.